Early Dynastic and Early Argonic administrative texts mainly from the Umma Region in the Cornell University cuneiform collections - Notizia, Palmiro 1980-; Visicato, Giuseppe; Cornell University (Bethesda, Maryland CDL Press, 2016)
Published and unpublished ED IIIb and Early Sargonic texts -- From the Umma Region -- Content of the texts -- City-rulers of Umma and chief administrators of the Temple of Inanna -- At Zabalam : the new evidence -- Unpublished ED IIIb - Early Sargonic texts -- From the Umma Region in CDLI -- Catalogue -- Concordance -- The texts -- Sheep -- Livestock -- Hides -- Fodder -- Ghee, cheese and lard -- Wool and garments -- Vegetables, fruit, flax, fish, timber, tools, military equipment -- Fields -- Personnel -- Sale documents and legal texts -- Metals -- Various contents -- Content not clear -- Barley, flour, bread, beer -- School texts -- Texts from the Adab Region and of uncertain provenance
Photos, transliterations, translations, and commentary on previously unpublished Sumerian cuneiform economic documents from mid-third-millennium Mesopotamia
Texts from the Adab Region and of uncertain provenance
Includes bibliographical references and indexes
Keywords: Cuneiform inscriptions, Sumerian -- Iraq; Cuneiform tablets -- Iraq; Cuneiform inscriptions, Sumerian -- Iraq; Cuneiform tablets -- Iraq; Civilization; Cuneiform inscriptions, Sumerian; Cuneiform tablets; Economic history; Iraq -- Economic conditions; Iraq -- Civilization -- To 634; Iraq -- History -- To 634; Iraq -- Economic conditions; Iraq -- Civilization -- To 634; Iraq -- History -- To 634 -- Iraq -- History